Review On Bacillus Species for Plant Pathogens as Versatile Weapons - Roshan Satpathy, Rakesh (International Journal of Psychosocial Rehabilitation, 2025)
Plant pathogens are the major threat for beneficial agricultural production. The three families of Bacillus lipopeptides - iturins, surfactins, and fengycins were primarily investigated for their antagonistic activity in a broad range of potential phytopathogens, including fungi, bacteria and oomycetes, in the frame of biological control of plant diseases. Chemical-based pesticides are currently considered to be reliable and an effective step for the control of agricultural pests. Chemical pesticides are vastly effective and suitable to use, but they pose a potential threat to the environment and life on earth of all kinds. The use of biological control agents for plant pathogens management is therefore considered as a more efficient and sustainable method for secure and beneficial agricultural productivity. In the field of biopesticides, biocontrol agents based on Bacillus plays a fundamental role.Many species of Bacillus have been shown to be effective against a wide range of plant pathogens. The goal of this paper is to present biocontrol potential of Bacillus species relative to their antagonizing characteristics to plant pathogens.